Bilingualism and Aging: Implications for (Delaying) Neurocognitive Decline - Gallo, Federico; DeLuca, Vincent; Prystauka, Yanina; Voits, Toms; Rothman, Jason; Abutalebi, Jubin (Frontiers in Human Neuroscience, 2022)
As a result of advances in healthcare, the worldwide average life expectancy is steadily increasing. However, this positive trend has societal and individual costs, not least because greater life expectancy is linked to higher incidence of age-related diseases, such as dementia. Over the past few decades, research has isolated various protective ‘healthy lifestyle’ factors argued to contribute positively to cognitive aging —e.g., healthy diet, physical exercise and occupational attainment. The present article critically reviews neuroscientific evidence for another such factor, i.e., speaking multiple languages. Moreover, with multiple societal stakeholders in mind, we contextualize and stress the importance of the research program that seeks to uncover and understand potential connections between bilingual language experience and cognitive aging trajectories, inclusive of the socio-economic impact it can have. If on the right track, this is an important line of research because bilingualism has the potential to cross-over socio-economic divides to a degree other healthy lifestyle factors currently do not and likely cannot.